Influence of implant connection on the stress distribution in restorations performed with hybrid abutments - Tribst, J. P.M. [UNESP]; Dal Piva, A. M.O. [UNESP]; Anami, L. C.; Borges, A. L.S. [UNESP]; Bottino, M. A. [UNESP] (My University, 2019)
Aim This study evaluated the influence of prosthetic connection type (external hexagon [EH], internal hexagon [IH] and morse taper [MT]) on the stress distribution in an implant-supported prosthesis. Materials and methods Using modeling software, three sets were formed according to the prosthetic connection composed of ceramic crown, mesostructure, abutment, abutment screw, implant, cement layers and bone tissue. Solids were imported to the analysis software and bone model was fixed in the base. All materials were considered isotropic, linearly elastic and homogeneous. The static load (500 N, 30°) was applied in the central fossa. Stress distribution data were obtained according to Von-Mises and microstrain criteria. Results The type of prosthetic connection influenced the stress distribution. The stresses for the IH and MT connections were concentrated on the implant and abutment; for EH at the implant, abutment screw, at the implant platform, and at the cement layer between abutment and mesostructure. There is lower influence for the crown and mesostructure, with more promising results for the MT connection. For the bone tissue, all connections showed the same strain pattern. Stress peaks of 148, 142 and 138 MPa in the implant, 134, 129 and 62 MPa in the screw, and 86, 118 and 131 MPa were observed respectively for EH, IH and MT. Conclusions The morse taper connection showed promising performance with lower stress concentration in the abutment screw, implant platform and cement layers.
Keywords: Dentalimplant-abutment design; Finiteelementanalysis; KEYWORD Dentalimplants